Decrease in Hospitalizations for Pneumonia in Children under Five Years of Age in an Indian Reservation in Panama after the Introduction of the Heptavalent Pneumococcal Conjugate Vaccine (PCV7) - Javier Nieto Guevara; Carlos Daza; Rebecca Smith (International Journal of Pediatrics)
This study quantifies the impact of Heptavalent-Pneumococcal Conjugate Vaccine (PCV7) in Panama on indigenous children younger than 5 years old, based on clinical pneumonia cases. This study demonstrates a significant 41.2% reduction in hospitalizations and 38.6% reduction in referrals for pneumonia following the introduction of PCV7. Burden of disease from pneumonia appears reduced in the ≤12-month- and 13-to-24-month-old groups.